2015
DOI: 10.11646/phytotaxa.192.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus section Brunneopicti: a phylogenetic reconstruction with descriptions of four new taxa 

Abstract: Agaricus is a genus of saprobic basidiomycetes including species of nutritional and medicinal interest. Historically the temperate species have been grouped into eight classical sections. Recent phylogenetic analyses however, revealed that two-thirds of the tropical taxa do not cluster in these sections, but form exclusively tropical clades. Seven (TR I to TR VII) strongly supported tropical clades have been revealed and it was hypothesized that clade TR I might represent Agaricus section Brunneopicti. This se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 25 publications
(46 reference statements)
0
32
0
Order By: Relevance
“…The macroscopic characters were recorded according to the methodology described by Largent (1986) . KOH and Schäffer’s reactions were performed as described by Chen et al (2015) . Micromorphological features were examined from dried specimens following the protocols of Largent et al (1977) including anatomy of lamellae, pileipellis and partial veil, and features of basidiospores, basidia and cystidia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The macroscopic characters were recorded according to the methodology described by Largent (1986) . KOH and Schäffer’s reactions were performed as described by Chen et al (2015) . Micromorphological features were examined from dried specimens following the protocols of Largent et al (1977) including anatomy of lamellae, pileipellis and partial veil, and features of basidiospores, basidia and cystidia.…”
Section: Methodsmentioning
confidence: 99%
“…In the field, Agaricus species are easily distinguishable by having a fleshy pileus with free lamellae which produce brown spores, and an annulate stipe. The taxonomy of the genus has been well developed during the last two decades by using molecular phylogenetic tools ( Challen et al 2003 , Kerrigan et al 2005 , 2008 , Zhao et al 2011 , Parra 2013 , Thongklang et al 2014 , Chen et al 2015 , Gui et al 2015 ), which essentially reshaped our understanding of some of the morphologically recognized sections. The internal transcribed spacer (ITS) region of the nuclear ribosomal DNA has been largely used for establishing the phylogenetic relationships among the members of the genus, for example, in the phylogenetic study of Zhao et al (2011) , an eight-section taxonomic system was well supported, including seven additional strongly supported clades (TRI to TRVII).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agaricus L. (Agaricaceae, Agaricales) is a genus more than 400 species right now (Zhao et al 2011, 2012; Chen et al 2012, 2015; Lebel & Symel 2012; Lebel 2013; Li et al 2014; Gui et al 2015; Liu and Hyde 2015; Wang et al 2015). It is also a valuable genus and contains a lot of important species, such as the famous cultivated mushrooms A. bisporus (J. E. Lange) Imbach and A. subrufescens Peck.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phylogenetic analysis on Agaricus from tropical areas revealed 11 new lineages (Zhao et al 2011). The deeply phylogenetic studies on those new lineages indicated that several sections had been reconstructed or recognised, such as sections Brunneopicti , and Nigrobrunneoscentes (Chen et al 2015; Wang et al 2015). …”
Section: Introductionmentioning
confidence: 99%